Determination of Quality Index for Surface and Ground Water of Jashore, Bangladesh (Annals of Bangladesh Agriculture, 2022)
The purpose of present study was to estimate the water quality index (WQI) for describing water quality of both surface water and groundwater of Jashore, Bangladesh. The samples were collected from pond and tube-well water of the campus area of Jashore University of Science and Technology and Bhairab river, Jashore in February 2019. The collected samples were analyzed to calculate WQI from the following parameters: pH, electrical conductivity, total alkalinity, total suspended solids, total dissolved solids, dissolved oxygen, total hardness, chloride ions, biological oxygen demand, and sulphate ions. WQI values found in this study for tube-well, pond and river water samples were in the range of 43-47, 61-85, and > 100 which demonstrate the status of water as good, poor, and polluted, respectively. The published results obtained from this investigation may acquaint the residents of the research area about using the water mainly in drinking purpose.Ann. Bangladesh Agric. (2021) 25 (1) : 117-122